Epstein–Barr virus–host cell interactions: an epigenetic dialog? - Niller, Hans H.; Szenthe, Kalman; Minarovits, Janos (Frontiers in Genetics, 2014)
Here, we wish to highlight the genetic exchange and epigenetic interactions between Epstein–Barr virus (EBV) and its host. EBV is associated with diverse lymphoid and epithelial malignancies. Their molecular pathogenesis is accompanied by epigenetic alterations which are distinct for each of them. While lymphoblastoid cell lines derived from B cells transformed by EBV in vitro are characterized by a massive demethylation and euchromatinization of the viral and cellular genomes, the primarily malignant lymphoid tumor Burkitt’s lymphoma and the epithelial tumors nasopharyngeal carcinoma and EBV-associated gastric carcinoma are characterized by hypermethylation of a multitude of cellular tumor suppressor gene loci and of the viral genomes. In some cases, the viral latency and oncoproteins including the latent membrane proteins LMP1 and LMP2A and several nuclear antigens affect the level of cellular DNA methyltransferases or interact with the histone modifying machinery. Specific molecular mechanisms of the epigenetic dialog between virus and host cell remain to be elucidated.